2012
DOI: 10.1308/003588412x13373405385494
|View full text |Cite
|
Sign up to set email alerts
|

Patch variability following carotid endarterectomy: a survey of Great Britain and Ireland

Abstract: INTRODUCTIONEvidence suggests a clinical benefit with patch angioplasty after carotid endarterectomy (CEA). The UK National Vascular Database has demonstrated variation in practice but does not record technical details. This study was intended to define indications and technique of patching after CEA.METHODSAn electronic questionnaire was emailed to all 402 members of the Vascular Society of Great Britain and Ireland. The email could not be received by 23 and 14 did not perform CEA. Some questions allowed mult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…30,31 Despite those recommendations, a survey of vascular surgeons reported that individual preferences on this issue still vary widely. 32 Hemodynamics is a determining factor in the growth of carotid atheromatous disease. Regions affected by low and oscillating WSS are associated with monocyte activation, increased vasoconstriction, oxidative stress, higher cellular turnover, and apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…30,31 Despite those recommendations, a survey of vascular surgeons reported that individual preferences on this issue still vary widely. 32 Hemodynamics is a determining factor in the growth of carotid atheromatous disease. Regions affected by low and oscillating WSS are associated with monocyte activation, increased vasoconstriction, oxidative stress, higher cellular turnover, and apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…The general view is that the patch closure method minimizes the risk of perioperative and long-term stroke and restenosis, compared to the primary closure method; however, the existence of controversial results requires more studies to support these findings. [7,8,[16][17][18] There is still no consensus among the surgeons about the closure technique and, therefore, each surgeon decides on the closure technique based on his or her own experience. In the present study, we found no statistically significant difference in the perioperative results, except for hematoma, between the two groups.…”
Section: Discussionmentioning
confidence: 99%